Prognostic value of CMR parametric mapping in cardiac amyloidosis: an updated systematic review and meta-analysis - Adam Ioannou; Jawdat Abdulla; Muhammad Umair; Seyed Ali Forouzannia; Seyedeh Romina Rafiei Alavi; Seyed Mohammad Forouzannia; Giulia Francese (Open Heart)
Background Cardiac amyloidosis (CA) is the leading cause of mortality in systemic amyloidosis, highlighting the need for accurate risk assessment to guide patient management. While the diagnostic value of cardiac MR (CMR) parametric mapping is well established, its prognostic utility remains inconsistent across studies. To perform a systematic review and meta-analysis to evaluate the prognostic value of CMR parametric mapping in predicting all-cause mortality, heart failure hospitalisation and major adverse cardiovascular events in patients with CA.Methods An extensive search was conducted in Medline, Scopus, Embase and Web of Science databases. Eligible studies were observational studies that reported HRs for predicting predefined outcomes in patients with CA using CMR parametric mapping.Results 22 studies with 3398 patients were included in this systematic review. Higher extracellular volume (ECV) values were associated with increased mortality, both as a dichotomous (HR: 2.90; 95% CI: 1.68 to 5.01) and continuous variable (HR for 1% increase: 1.08; 95% CI: 1.06 to 1.10; HR for 3% increase: 1.17; 95% CI: 1.11 to 1.22 and HR for 10% increase: 2.11; 95% CI: 1.70 to 2.62). Higher native T1 mapping values were associated with mortality as a dichotomous variable (HR: 1.33; 95% CI: 0.79 to 2.24). Native T2 mapping showed inconsistent associations with prognosis across studies.Conclusions Higher ECV and native T1 values are associated with worse prognosis in CA, supporting their role in risk stratification. Further studies with standardised CMR protocols are needed to enhance the prognostic utility of parametric mapping in clinical practice.